PENGARUH TERAPI MUSIK KLASIK TERHADAP KECEMASAN PADA PASIEN PRA OPERASI DI RSUD DR. M. YUNUS BENGKULU - Ida Rahmawati; Fernalia Fernalia; Ani Safitria (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: Surgery is an invasive procedure by making an incision due to certain indications. Patients who will undergo surgery tend to have high anxiety. Purpose: This study aims to determine the effect of music therapy on preoperative patient anxiety at RSUD Dr. M. Yunus Bengkulu. Method: The study design used a pre-experimental design with one group pretest post test. The population in this study were all preoperative patients in the Flamboyan room of RSUD Dr. M. Yunus Bengkulu. Samples in the study of pre-operative patients who were met during the study were 32 people. the sampling technique uses accidental sampling. Sample criteria include: preoperative patient major surgery. Data collection techniques using primary data in the form of preoperative questionnaires for anxiety measurement. Anxiety questionnaire that HARS (Hamilton Anxiety Rating Scale). The statistical test used is the t-test. Results: The results showed that p = 0,000 <0.05 was significant. There is a significant influence of musik therapy on surgery patient anxiety in Dr. M. Yunus Bengkulu. Conclusion: Musik therapy provides a relaxation response to the body so that it can reduce anxiety levels. It is hoped that nurses can provide modality therapies such as musik therapy to preoperative patients, in order to reduce anxiety that occurs during the operating room.Keywords: Anxiety; Classical musik therapy; Preoperativ